Effect of High Voltage Pulsed Current on the integration of total skin grafts in rats submitted to nicotine action. Issue 3 (August 2019) - Souza, Ana Karina; Souza, Tamires Rodrigues; Siqueira das Neves, Lais Mara; de Paula Marcondes Ferreira Leite, Gabriela; Garcia, Sérgio Britto; Roberto de Jesus Guirro, Rinaldo; Barbosa, Rafael Inácio; Caldeira de Oliveira Guirro, Elaine
Abstract: Objective: The aim of this study was to evaluate the impact of High Voltage Pulsed Current (HVPC) on the integration of total skin grafts in rats submitted to nicotine action. Materials and methods: For this purpose, 60 adult Wistar rats randomly distributed in 6 groups of 10 animals were analyzed. The electrical stimulation (anodic and cathodic stimulation, motor level, 30 min at 10 Hz; minimum voltage 20 μs and 100 μs pulse interval) was applied for seven days, starting on the third day after surgery and after the dressing was removed from the graft. Results: Anodic HVPC promoted greater graft integration, demonstrating a lower percentage of tissue contraction, a lower number of inflammatory infiltrates and a greater amount of vascular endothelial growth factor (VEGF), as well as a higher number of newly formed blood vessels. Conclusions: HVPC can positively influence the integration of skin grafts in nicotine-treated rats. anodic HVPC is shown to promote greater integration in relation to a lower percentage of tissue contraction, a lower number of inflammatory infiltrates and a greater amount of vascular endothelial growth factor and newformed blood vessels. Whereas, the cathodic polarity has presented smaller amount of tissue gap. Highlights: High voltage electrical stimulation can positively influence in the integration of skin graft under efect of nicotine. Differents polarities of high voltage electrical stimulation improve the integration of the skin graft in rats submitted to nicotine. Anodic polarity was more effective in the skin graft under influence of nicotine. The cathodic and anodic polarity was influence in the viability of skin graft under influence of nicotine.